TRANSFORMASI HUKUM HINDU DALAM PEMBANGUNAN HUKUM NASIONAL DI TENGAH DINAMIKA KEHIDUPAN SOSIAL BUDAYA - Ni Luh Gede Hadriani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
The development of law in our country is still running imperfectly behind the dynamic social and community culture that is developing. The development of community life is very rapid due to the advance in science and technology coupled with a very open of digital and social media world. The development of community life should be followed by the law developments needed by the community, thus a sense of justice in the law can be felt by the whole community. This fact is one of the sources of the irregular of law in Indonesia. By looking at these conditions, the transformation of Hindu law in the development of national law needs to be conceived, reviewed and developed by the law enforcers. The law should be established in line with the socio-cultural structure and values of our nation's local wisdom, but it can still accommodate the dynamics of social and cultural life in the era of openness as it is today. Through this, the Hindu law is expected to contribute to the development of national law. With the contribution of Hindu Law to National Law, it is expected that a sense of justice can be felt by the whole community.